Outlines of sociology /edited by lrving L. Harowitz - "Gumplowicz, Ludwig" (New York, 1963)
This book contains following topics:The history of Sociology: Auguste Comte; Lambert Quetelet; Herbert Spencer; Paul Henri Theiry holbach; Albert Schaffle; Paul von Lilienfeld; Adolf Bastain: Foundations and Fundamentals of Sociology; the three classes of Phenomena; Universal laws; Concept function and scope of sociology.
Keywords: Sociology